PENGARUH PENERAPAN MODEL GROUP INVESTIGATION PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR SISWA - Winanti, Lisdiah; Rosnita, Rosnita; Tampubolon, Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the influence of the application Group Investigation learning model on student learning outcomes in class XI of SMA Raya 2 Sungai Raya. The research method used is an experimental method with quasi-experimental. sample used in this study were students of class XI IPS 1 (experimental class) totaling 35 students and class XI IPS 3 (control class) totaling 36 students.The results of the study were the average value of the control class student learning outcomes using an expository model of 72.39 and a standard deviation of 11.94, while the average student learning outcomes of the experimental class used a group investigation model of 81.01 and a standard deviation of 11.60. From the average learning outcomes of students who use the expository model using the investigation group model there is a difference of 8.62. The results of the calculation of the t test obtained t count the final test data of 4.6036 while t table (5 = 5%) of 1.997, it can be seen t count> t table concluded that Ha is accepted. From the calculation of Effect size (ES) obtained by 0.74 with high criteria. The conclusion of this study means that the application of the investigation group model has a high influence on student learning outcomes in learning geography class XI SMA Negeri 2 Sungai Raya. Keywords: Influence,Group Investigation of Models, Learning Outcomes, Geography